Lucy: um ambiente para aulas práticas de computação ubíqua - Peixoto, Maria Joelma Pereira (2017)
Mark Weiser coined the term Ubiquitous Computing (UbiComp) describing a future in which everyday-life objects would have embedded computers providing services anytime and anywhere. One of the hardest activities in teaching UbiComp is putting into practice the theory knowledge of this discipline. In fact, current UbiComp tools require high programming skills or are not carefully designed for educational purposes. We implemented a survey with 15 professors and 60 postgraduate and undergraduate students from 16 universities. According to this survey, the two most challenging Ubicomp concepts to explain were: context-awareness and middleware platforms. Results also showed professors’ difficulty in finding tools to assist the practical teaching of UbiComp’s concepts. Therefore, this work presents the design, develop, and evaluation of a Virtual Learning Environment, called Lucy (Learning Ubiquitous Computing Easily), which aids UbiComp practical classes. Lucy has two main elements: a Web tool and an Android mobile app. The former provides UbiComp theoric materials, videos, practices, and simulations. The latter uses smartphones features and sensors to run simulations of UbiComp concepts. These simulations follow settings configured by the Web tool. We evaluated Lucy during Context-Awareness classes in UbiComp courses, at the same university, along three distinct semesters. We had a total of twenty students that experienced the environment. In the first two evaluations, we gathered information about Lucy’s pedagogical issues. Then, we performed a more formal usability test and a semistructured interview concerning the student learning process. Results showed improvements in students reasoning about UbiComp concepts after Lucy practices sessions. Besides, the environment helped the debate and interaction among students. The overall result of the usability test was satisfactory, with the average score of 80 out of 100 points, according to the System Usability Scale (SUS). This result indicates a software with a good usability.